Definicja legalna działalności gospodarczej z Ordynacji podatkowej a determinanty jej formułowania - Borszowski, Paweł (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
The article analyzes one of the key issues when it comes to the application of legal definitions in the tax law. The tax legislator, regardless of the fact that the legal definition of economic activity was introduced in the provisions of public commercial law, formulates its own definition of this concept in general tax law. In such a case, the determinants of formulating the definition of legal business activity in the Tax Ordinance Act should be determined.Two determinants were chosen and the defi nition of economic activity from the Tax Ordinance Act was analyzed from this point of view. The hypothesis was confirmed that the tax legislator did not use these determinants. For tax theory and practice, this makes it necessary to assess whether a definition of this concept is needed in general tax law.
Keywords: definicja prawna; działalność gospodarcza; determinanty formułowania definicji w prawie podatkowym